2015
DOI: 10.1007/s13277-015-4256-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA small nucleolar RNA host gene 12 (SNHG12) promotes cell proliferation and migration by upregulating angiomotin gene expression in human osteosarcoma cells

Abstract: The long non-coding RNA (lncRNA) small nucleolar RNA host gene 12 (SNHG12) has a role in cell proliferation and migration. Angiomotin, encoded by the AMOT gene, is a protein that regulates the migration and organization of endothelial cells. SNHG12 and AMOT have been shown to play a role in a variety of human cancers but have yet to be studied in detail in human osteosarcoma. Tissue samples from primary osteosarcoma (n = 20) and adjacent normal tissues (n = 20), the osteosarcoma cell lines, SAOS-2, MG-63, U-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 30 publications
2
82
0
Order By: Relevance
“…To explore the potential mechanism underlying the effects of SNHG12, an FCM assay determined that silencing SNHG12 expression promoted apoptosis and inhibited migration and invasion of cervical cancer cells. Our results confirmed that the overexpression of SNHG12 promoted cell proliferation and migration and inhibited apoptosis [16-18]. Our study expanded upon the current knowledge of the downstream regulatory mechanism of SNHG12.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To explore the potential mechanism underlying the effects of SNHG12, an FCM assay determined that silencing SNHG12 expression promoted apoptosis and inhibited migration and invasion of cervical cancer cells. Our results confirmed that the overexpression of SNHG12 promoted cell proliferation and migration and inhibited apoptosis [16-18]. Our study expanded upon the current knowledge of the downstream regulatory mechanism of SNHG12.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have found that SNHG12 expression was increased in and contribute to the metastasis of several types of cancer [16-18]. We assessed the effect of SNHG12 on cervical cancer cells, and we observed that the downregulation of SNHG12 led to a significant decrease in the migratory and invasive capacities of the cells (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…57,58 Similarly, a recent study illuminated that the level of SNHG12 in CRC tissues is higher than the adjacent normal mucosa as detected by qRT-PCR. Furthermore, upregulation of SNHG12 was distinctly associated with larger tumor size, advanced tumor stage, and worse 5-year survival rate in CRC patients.…”
Section: Small Nucleolar Rna Host Gene 12mentioning
confidence: 93%
“…High SPRY4-IT1 expression has been observed in renal cancer and down-regulation of SPRY4-IT1 reduces renal cancer cell proliferation, invasion and migration (10). EWSAT1 and SNHG12 were all found to be up-regulated in OS and act as tumor promoter (11,12).…”
Section: Introductionmentioning
confidence: 99%